PENGARUH DIAMETER SCREW SEBAGAI MIXER TERHADAP KAPASITAS PRODUKSI MIE BASAH - ., Muhyin; Suryanto, Wsnu (MEKANIKA: Jurnal Teknik Mesin, 2015)
Wet noodles as one of the basic human needs, has a fairly large market, one where the processing of wet noodles is in the area of Surabaya precisely in the village alley jojoran 5 surabaya.dari field survey results in thetreatment process using a manual process with a capacity of 15kg / jam.Untuk increase capacity should bedeveloped and implemented appropriate technology, so came the idea to create a tool maker author noodles using ascrew conveyor system with motor in order to increase the production capacity of wet noodles .. In this case theauthor analyzes the analysis of the influence of rotation of the motor and the diameter of the screw as a mixer to wetnoodle production capacity.In this study discussed the analysis of motor rotation and diameter of the screw as amixer for basah.dimana noodle production capacity of analysis and diameter divariabelkan round following around of 20 rpm, 40 rpm, 60 rpm and a screw diameter of 60 mm, 70 mm, 80 mm. Analysis of the data and theresults of the test showed that the average maximum capacity with appropriate quality standards are achieved wetnoodle consumption of 48,9kg / h on lap 20 rpm and a screw diameter of 80 mm.Keywords : wet noodle, screw diameter, round and capacity